FRI0296 Single center experience with 300 systemic lupus erythematosus patients. (15th June 2017) - Tekeoglu, S; Karadag, D Temiz; Isik, O Ozdemir; Yazici, A; Cefle, A
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease with diverse clinical manifestations. Objectives: Here, we present 300 patients with SLE attending our clinic between 2001 and 2017. Methods: Demographics, clinics, laboratory findings, Systemic Lupus International Clinics (SLICC)/American College of Rheumatology (ACR) damage index scores and treatments were analyzed. Diagnosis was confirmed with 1997 ACR (1) or 2012 SLICC (2) classifications. Descriptive statistical tests were used for analysis. Results: Demographics and clinical characteristics are presented in Table 1. Anti-dsDNA was positive in 185 (61.6%), anti-Sm was positive in 35 (11.6%), anti-phospholipid antibodies was positive in 67 (22.3%), direct Coombs test was positive in 69 (23%) patients. Complement levels were low in 171 (57%) patients. In patients with renal disease, class IV lupus nephritis was the most common form (37 patients [12%]) followed by class II nephritis (34 patients [11%]). Forty-six patients had antiphospholipid syndrome. Treatments patients ever received are presented in Table 2. Cyclophosphamide treatment was given mostly for renal disease. Within 22 patients receiving rituximab, 2 had thrombocytopenia and 1 had hemolytic anemia unresponsive to other treatments, 1 had protein-losing enteropathy and 1 had lupus enteritis; the rest had lupus nephritis. One patient received intravenous immune globulin (IVIG) for severe neutropenia and 2 patients for severe thrombocytopenia. One patient received plasmapheresis for vasculitis. One patient received IVIG, plasmapheresis, rituximab for severe renal failure, alveolar hemorrhage requiring intensive care unit admission and 1 patient received same treatment for severe unresponsive hemolytic anemia. Conclusions: In long term, SLICC/ACR damage index was highest in patients received pulse steroid for renal disease (min:0, max:5). Four (1.3%) patients had pulmonary hypertension, 31 (10.3%) had avascular necrosis, 24 (8%) had viral infections requiring treatment or bacterial infections requiring admission due to immunosuppression, 12 (4%) had malignancy. SLE is an autoimmune disease requiring multi-faceted approach. References: ) Hochberg MC: Updating the American College of Rheumatology revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum. 40:1725 1997. ) Petri M, Orbai AM, Alarcon GS, et al.: Derivation and validation of the Systemic Lupus International Collaborating Clinics classification criteria for systemic lupus erythematosus. Arthritis Rheum. 64:2677–2686 2012. Disclosure of Interest: None declared